Synthesis of Some new Triazino-Thiadiazolos and Thiadiazolo-Quinazoles as Antifungal Agents - Dwivedi, Vandana; Tiwari, Nirupama; Agarwal , R.K. (Asian Journal of Chemistry, 2010)
Some new 2-aryloxymethyl-5 substituted 1 ,3,4-thiadiazolo[3,2-a]-1 ,3,5-triazine-7-thiaones (IIIa-e) and 2-aryloxymethyl-1,3,4-thiadiazolo[2,3-b] quinazolin-4-ones (Va-e) have been prepared. These compounds have been screened for their antifungal activity against two fungi viz. Aspergillus niger and Helminthosporium oryzae at 1000, 100 and 10 ppm concentration. A possible structure activity relationship has been discussed.